English curriculum analysis and its relevance to Islamic boarding school goals - Rina Lestari; Emi Emilia (Universitas Pendidikan Indonesia, 2023)
This case study reports on the analysis of the national curriculum known as curriculum 2013, and its relevance to a modern Islamic boarding school goals. This study involved one Islamic senior high school in West Java, Indonesia. The qualitative data were derived from curriculum 2013 and the curriculum complementary documents designed by the curriculum development department of the school. This document analysis relied on four fundamental elements of curriculum introduced by Tyler (1949), those are educational goals, learning experiences, learning organizations, and learning evaluations. The results showed that four fundamental aspects of the curriculum 2013 were in line with the Tyler curriculum principles. A minimum TOEFL score is one of the objectives, but the programs are inadequate to prepare the students to achieve it. Likewise, the final evaluation for the objective is still inconsistent due to the test cost issue. However, the curriculum 2013 supported by some complementary programs has demonstrated its relevance to the goals of the modern Islamic boarding school.